Wardrobe or agency? Gender representation in 5 action videogames of the seventh generation (2019)
This work conducted a quantitative study of gender representation in five top-selling multiplatform action video games leading in sales of the seventh generation, through the technique of content analysis. The central narrative of each game was analyzed by using the character as an analysis unit and the mission as a registration unit; the latter is taken as each section of the game in which the player needs to achieve a goal to progress through the story. The physical appearance, behavior, language and dress of both masculine and feminine leading, supporting and tertiary characters were categorized. A 4:1 ratio between male and female characters was found, which comprises a serious under-representation of the female gender in these games. Significant differences were also found in both physical and behavioral representation between male and female characters. Regarding physical appearance, it was found that female characters’ outfits are noticeably more revealing than those of male ones. Concerning behavior, female characters were found to have a greater presence of sexualized behaviors and to have less confidence, violence and leadership attitude than their male counterparts. It is claimed that, despite what has been found, gender representation in the media has improved when compared to the findings of previous studies, and that it is necessary to do research on the way in which players relate to these contents.